ANALISIS KONEKSI DAN RELEVANSI PEMIKIRAN KI HADJAR DEWANTARA DI DUNIA PENDIDIKAN - Anang Fathoni; Ana Andriani (Journal of Professional Elementary Education, 2023)
The central figure of education as well as an educator whose rationale was able to surpass his time was Ki Hadjar Dewantara. Critical analysis is needed in order to connect the intellectual heritage of Ki Hadjar Dewantara which is currently manifestly socialized as the foundation of the Kurikulum Merdeka. Thus, the purpose of this study is to examine the relevance of Ki Hadjar Dewantara's thoughts in the world of education. The research used in this study is included in the type of literature review or literature review. The steps in this study are 1) establishing the research topic; 2) collecting references; 3) classifying and reducing references relevant to the research topic; 4) conducting studies and analyses by marking important discussions in the reference; 5) writing down the results. The results of the study show that the thought of Ki Hadjar Dewantara has relevance and connection with other figures such as John W. Santrock in three aspects of child development, Albert Bandura in modeling theory, and Paulo Freire in educational independence. Then, the internalization of Ki Hadjar Dewantara's thinking in education in Indonesia became a good solution to improve the quality of Indonesian national education